Los Angeles: One Domestic Viewpoint - Annie Chu; Rick Gooding (Oz, 2002)
The image of Los Angeles: being on the edge of the continent, the extroverted city of image makers, where novelty supplants meaning. There is yet for those who choose to work here, a complex stew of initiatives and interests that compels one to stay and seek out her meaning.